Functional Characterization of a Gene in Sedum alfredii Hance Resembling Rubber Elongation Factor Endowed with Functions Associated with Cadmium Tolerance - Liu, Mingying; Qiu, Wenming; He, Xuelian; Zheng, Liu; Song, Xixi; Han, Xiaojiao; Jiang, Jing; Qiao, Guirong; Sang, Jian; Liu, Mingqing; Zhuo, Renying (Frontiers in Plant Science, 2016)
Cadmium is a major toxic heavy-metal pollutant considering their bioaccumulation potential and persistence in the environment. The hyperaccumulating ecotype of Sedum alfredii Hance is a Zn/Cd co-hyperaccumulator inhabiting in a region of China with soils rich in Pb/Zn. Investigations into the underlying molecular regulatory mechanisms of Cd tolerance are of substantial interest. Here, library screening for genes related to cadmium tolerance identified a gene resembling the rubber elongation factor gene designated as SaREFl. The heterologous expression of SaREFl rescued the growth of a transformed Cd-sensitive strain (ycf1). Furthermore, SaREFl-expressing Arabidopsis plants were more tolerant to cadmium stress compared with wild type by measuring parameters of root length, fresh weight and physiological indexes. When under four different heavy metal treatments, we found that SaREFl responded most strongly to Cd and the root was the plant organ most sensitive to this heavy metal. Yeast two-hybrid screening of SaREFl as a bait led to the identification of five possible interacting targets in Sedum alfredii Hance. Among them, a gene annotated as prenylated Rab acceptor 1 (PRA1) domain protein was detected with a high frequency. Moreover, subcellular localization of SaREF1-GFP fusion protein revealed some patchy spots in cytosol suggesting potential association with organelles for its cellular functions. Our findings would further enrich the connotation of REF-like genes and provide theoretical assistance for the application in breeding heavy metal-tolerant plants.